Integrating information and communication technology in open and distance learning delivery at the distance learning centre, University of Ibadan, Nigeria (2022)
The study investigated the integration of Information and Communication Technology Learning Applications (Learning Applications, Google Applications and Social Media Applications) on the learning effectiveness of learners at the Distance Learning Centre, University of Ibadan. The descriptive survey research design was adopted while the population comprised 100 - 500 level, - with a sample size of 150 students randomly selected from the faculties of Arts, Education and the Social Sciences. A 45- items questionnaire on Perceived Information and Communication Technology Learning Applications on Learning Effectiveness in Distance Education Inventory with reliability coefficient of 0.78 was used. Data were analyzed using descriptive statistics of frequency counts, simple percentages, analysis of variance (ANOVA), mean and standard deviation analysis at 0.05 level of significance. The findings of the study revealed that the ICT Learning Applications (Learning Applications, Google Applications and Social Media Applications) significantly influenced students' Learning Effectiveness (F (3, 145) = 122.669; R2 = 0.71), and jointly accounted for 71.2% of its variance. Based on the findings, it was recommended that the management of the Distance Learning Centre, University of Ibadan should improve on using these Information Communication Technologies by maximizing them to facilitate effectual output on learners' academic achievement.